Avaliação de mediadores pró-inflamatórios, próresolutivos e da via de sinalização ERK1/2 em modelo murino de infecção por Leishmania spp - Leandro Gonzaga de Oliveira (2018)
In this study, we propose to investigate, in a comparative and kinetic way, the inflammatory responses, especially the MAP kinase ERK 1/2 pathway, after infection of BALB/c mice by Leishmania braziliensis or L. amazonensis, resistance and susceptibility models, respectively. Our findings demonstrated that, in the resistance model, the kinetics of ERK1/2 activation follows the course of the infection, with peak activation at the apex of tissue parasitism, being accompanied by increased NF-kB activation and elevated IFN-, IL-10 and IL-4, followed by reduction in the resolution phase. In L. amazonensis infection, there is a temporary deficiency in ERK1/2 phosphorylation, in the late stages of infection, resulting in increased lesion, parasitism and inflammation, activation of specific immune response, NF-kB and caspase 3. This fact led us to investigate how the activation of ERK1/2 could affect the progression of the disease in L. amazonensis infected animals. Using the MEK/ERK inhibitor, U0126, we verified that inhibition of this pathway resulted in bigger lesions and parasitic loads, in relation to the control animals. The role of the annexin A1 (AnxA1), a protein that has an anti-inflammatory action and importance in the resolution of inflammatory processes, was also evaluated in the infection by both species. In the absence of AnxA1, mice infected with L. braziliensis were able to control parasite replication but had more intense inflammatory responses and a delayed ability to decrease the size of their lesions. Our findings also showed higher levels of AnxA1 in serological samples from patients with mucosal leishmaniasis, which is characterized by a more intense inflammatory process, compared to the localized cutaneous form. Similarly, L. amazonensis infection of AnxA1KO animals leads to a more intense cellular infiltrate and larger and progressive lesions, but no effect on parasite loads. Taken together, the kinetic and comparative data revealed significant aspects of resistance and susceptibility to Leishmania infection, potential targets for the development of new drugs and therapeutic approaches.